Runaway groom - Marshall, Lynne, 1949- (Fortunes of Texas. Hotel Fortune., 2021)
When Mark Mendoza discovers his fiancée cheating on him on their wedding day, he hightails it out of town. Megan Fortune is there to pick up the pieces--and to act as his faux girlfriend when his ex shows up. Mark swears he will never get involved again. Megan doesn't want to be a "rebound" fling. But they find each other irresistible. What's a fake couple to do?